TENCON '91. Region 10 International Conference on EC3-Energy, Computer, Communication and Control Systems
DOI: 10.1109/tencon.1991.712524
|View full text |Cite
|
Sign up to set email alerts
|

The Simulation Of Self-excited Induction Generators For Use In Remote Area Power Supplies

Abstract: This paper describes a method for accurately predicting the miriimum value of capacitance necessary to initiate self-excitation with a. stand alone induction generator.Final steady-state self-excitation voltages and frequencies are also calculated, for loaded and unloaded operation, taking into account rotor parameter variations with frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Singh et al [2] presented a review of g rid code requirements for wind power interconnection in various countries. Grantham et al [3] observed that in case of SEIG operation the final steady-state self-excitation voltages and frequencies were found varying with the load demand and causing poor quality of supply. Melicio et al [4] presented the harmonic behaviour of currents injected in the electrical network by wind generation using fast Fourier transform technique.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al [2] presented a review of g rid code requirements for wind power interconnection in various countries. Grantham et al [3] observed that in case of SEIG operation the final steady-state self-excitation voltages and frequencies were found varying with the load demand and causing poor quality of supply. Melicio et al [4] presented the harmonic behaviour of currents injected in the electrical network by wind generation using fast Fourier transform technique.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the excitation schemes [10][11][12] involve power electronic converters along with the capacitor bank connected at the IG terminal to supply the required reactive power to excite the IG. The field oriented technique or vector control methods [13,14] are used to maintain constant voltage and frequency for a range of load and speed [13,14].…”
Section: Introductionmentioning
confidence: 99%